Promotion and inhibition effect of K in rice husk during chemical looping gasification - Xin, Hongchang (2023)
K is the trace metal with the most content in biomass, which provides a dual effect of promotion on chemical looping gasification (CLG) and inhibition on oxygen carrier (OC) performance. However, the mechanism and boundary between promotion and inhibition of K remains unclear in biomass CLG. In this study, the dual effect of K on CLG performance is investigated under different K content, steam, K existence form and thermo-kinetics analysis. The results show that K can significantly promote CLG performance under low K-addition and accelerate agglomeration under 12 % K-addition. Compared with the pickling rice husk, the gas yield, carbon conversion efficiency and gasification efficiency of 2 % CH3COOK-AH is the highest and increases by 56.6 %, 67.7 % and 58.5 % in CLG. Moreover, the addition of steam can sufficiently utilize the promotion effect of CH3COOK and inhibit the formation of Fe2SiO4 and agglomeration. Furthermore, 6 % CH3COOK-AH has the highest gas yield of 0.79 Nm3/kg, carbon conversion efficiency of 41.6 % and gasification efficiency of 78.1 % during steam CLG, which are respectively 102.6 %, 25.3 % and 127.0 % higher than those of 2 % CH3COOK-AH in CLG. In addition, KCl-AH has more Fe2SiO4, serious agglomeration and lower CLG performance than CH3COOK-AH under high K-addition. According to the CLG performance and thermogravimetric analysis, the promotion of CH3COOK is stronger than that of KCl.